Optical characterization and bandgap engineering of flat and wrinkle-textured FA(0.83)Cs(0.17)Pb(l(1-x)Brx)(3) perovskite thin films - Tejada, A (2018)
The complex refractive indices of formamidinium cesium lead mixed-halide [FA0.83Cs0.17Pb(I1– xBrx)3] perovskite thin films of compositions ranging from x = 0 to 0.4, with both flat and wrinkle-textured surface topographies, are reported. The films are characterized using a combination of variable angle spectroscopic ellipsometry and spectral transmittance in the wavelength range of 190 nm to 850 nm. Optical constants, film thicknesses and roughness layers are obtained point-by-point by minimizing a global error function, without using optical dispersion models, and including topographical information supplied by a laser confocal microscope.